An Experimental Study of Laboratory Hybrid Power System with the Hydrogen Technologies - Daniel Minarik; Bohumil Horak; Petr Moldrik; Zdenek Slanina (Advances in Electrical and Electronic Engineering, 2014)
This paper presents very small laboratory hybrid photovoltaic-hydrogen power system. The system was primarily assembled to verify the operability of the control algorithms and practical deployment of available commercial hydrogen technologies that are directly usable for storage of electricity produced from renewable energy sources in a small island system. This energetic system was installed and tested in Laboratory of fuel cells that is located in the university campus of VSB-Technical University of Ostrava. The energetic system consists of several basic components: a photovoltaic field, accumulators bank, water commercial electrolyzer and compact fuel cell system. The weather conditions recorded in two different weeks as model weather and solar conditions are used as case studies to test the energetic system and the results for two different cases are compared each other. The results show and illustrate selected behaviour curves of the power system and also average energy storage efficiency for accumulation subsystem based on hydrogen technologies or at the energetic system embedded components. On the basis of real measurement and its evaluation the ideal parameters of the photovoltaic field were calculated as well as the hydrogen technologies for supposed purpose and the power requirements.